2013
DOI: 10.1002/lary.23944
|View full text |Cite
|
Sign up to set email alerts
|

18F‐FDG‐PET/CT for the Assessment of the Contralateral Neck in Patients with Head and Neck Squamous Cell Carcinoma

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
1
8
1
Order By: Relevance
“…These values are similar to those for the ipsilateral side. However, we were able to show a difference between the positive predictive value for the ipsilateral side (90%) and that for the contralateral side (66%), which is in line with other reports . Kim et al .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These values are similar to those for the ipsilateral side. However, we were able to show a difference between the positive predictive value for the ipsilateral side (90%) and that for the contralateral side (66%), which is in line with other reports . Kim et al .…”
Section: Discussionsupporting
confidence: 93%
“…However, we were able to show a difference between the positive predictive value for the ipsilateral side (90%) and that for the contralateral side (66%), which is in line with other reports. 13,15 Kim et al 15 on comparing the metabolic findings with the histological workup of neck dissection found 18 F-FDG PET/CT to be less sensitive in detecting contralateral neck metastases than ipsilateral neck metastases due to the lower incidence of metastases and smaller nodes on the contralateral side.…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the use of FDG PET/CT or PET/CT may improve cancer staging accuracy and alter the clinical management of cervical nodal or distant metastases in patients with HNSCC (13,14). Recent studies have reported that FDG PET/CT has reliable diagnostic value for depicting CNM from HN-SCC compared with conventional CT/ MR imaging (15)(16)(17). Studies from our institution showed that FDG PET/CT is superior to CT/MR imaging for depicting metastatic lymph nodes in the ipsilateral and contralateral neck (15).…”
Section: Head and Neck Imaging: Fdg Pet/ct And The Prognostic Value Omentioning
confidence: 99%
“…However, in studies that focus on the ipsilateral and contralateral cervical nodes, the performance of PET is lower for contralateral nodes. Kim et al [9] compared PET/CT with MR or CT for [10]. Both studies concluded that PET/CT could not be used to avoid contralateral neck surgery or radiotherapy for high-risk patients.…”
Section: Pretreatment Staging In Advanced Diseasementioning
confidence: 99%